Membrane Topology of the Escherichia coli AmpG Permease Required for Recycling of Cell Wall Anhydromuropeptides and AmpC β-Lactamase Induction - Chahboune, Aicha (American Society for Microbiology, 2005)
Escherichia coli, and presumably most other gram-negative bacteria, possesses an efficient protein machinery for recycling its peptidoglycan during cell growth. The major recycled peptidoglycan product is N-acetylglucosamine-1,6-anhydro-N-acetylmuramic acid-tetrapeptide. Its uptake from the periplasm into the cytoplasm is carried out via the AmpG protein, an intrinsic membrane protein. In gram-negative bacteria carrying an ampC β-lactamase-inducible gene on their chromosomes, the induction mechanism is directly linked to peptidoglycan recycling. After identification of the different putative hydrophobic segments by computing, the AmpG topology was experimentally determined by using β-lactamase fusion. In the proposed model, AmpG contains 10 transmembrane segments and two large cytoplasmic loops.